Identification and Analysis of Difficulty Factors in Learning Multiplication in Class III Students: Case Study at SD Negeri Pati Wetan 01 - Dhelia Anggita Ningrum; Hidayatun Nisak; Lovika Ardana Riswari (Elementaria: Journal of Educational Research, 2024)
This research is to provide an explanation of the difficulties associated with learning to calculate multiplication material. Descriptive qualitative research was conducted at SD Negeri Pati Wetan 01 in Pati District, Pati Regency in November 2023. From the data obtained in class III, there were 30 students who experienced difficulties, 6 students experienced difficulties. Tests, observations, and interviews are the data collection methods used in this research. The data is then analyzed through reduction, presentation and drawing conclusions. The results of the analysis found that students in class III at SD Negeri Pati Wetan 01 faced several obstacles in learning multiplication mathematics. Students have difficulty in basic multiplication, often make mistakes when writing numbers, have difficulty placing values in two-fold multiplications, have difficulty finding two-fold multiplications when calculating with the right steps, and have difficulty finding two-fold multiplications when calculating with the right steps.